1996
DOI: 10.1016/0735-1097(95)00613-3
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and antiarrhythmic drug modulation of ST segment elevation in patients with Brugada syndrome

Abstract: ST segment elevation in patients with Brugada syndrome was augmented by selective stimulation of alpha-adrenoceptors or muscarinic receptors or by class IA drugs but was mitigated by beta-adrenoceptor stimulation or alpha-adrenoceptor blockade. These responses might be explained by postulating the presence of an area of early repolarization or a local "depolarized" area in the ventricle causing ST segment elevation in this syndrome. Because only a small number of patients were studied, these possibilities need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
397
6
13

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 681 publications
(430 citation statements)
references
References 20 publications
14
397
6
13
Order By: Relevance
“…[7][8][9]13,14 Several studies have demonstrated that the ECG in patients with BS changes dynamically. 8,9,11,13 The configuration and degree of ST-segment elevation in the precordial leads change from day to day.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9]13,14 Several studies have demonstrated that the ECG in patients with BS changes dynamically. 8,9,11,13 The configuration and degree of ST-segment elevation in the precordial leads change from day to day.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 99%
“…11 Other clinical studies also suggest that an increase in vagal activity and a withdrawal of sympathetic activity might play an important role in the ST elevation and arrhythmogenesis in BS. 5,7,14,15 Experimental studies suggest that a transient outward current (Ito)-mediated action potential notch and loss of the action potential dome at the epicardium, but not at the endocardium, creates a transmural voltage gradient that might be responsible for the ST-segment elevation of BS. 2,4 Acetylcholine facilitates loss of the action potential dome by suppressing ICa and/or augmenting the potassium current, leading to accentuation of ST-segment elevation.…”
Section: Circulation Journal Vol70 July 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…The ST-segment elevation may also display a saddleback appearance, 11 and the VT in rare cases may be monomorphic. 12 ST-segment elevation is associated with a wide variety of benign, as well as malignant, pathophysiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the proband suffered from two apparently distinct conditions: NMS and Brugada syndrome. The autonomic nervous system has been implicated in both diseases 12,13 , and several case reports have described patients exhibiting clinical phenotypes of both NMS and Brugada syndrome [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%